Karakter Morfologi dan Identifikasi Molekuler dengan Menggunakan Marka Gen 12S rRNA pada Ikan Baronang (Siganus spp.) di Perairan Laut Selatan Pulau Lombok - Mahrus Mahrus; Abdul Syukur (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2020)
This study aims to obtain the certainty of the number of species of baronang fish (Siganus spp.) Siganidae family in the waters of the south sea of Lombok Island.  This study used a sample of 90 fish from the fishermen's catch. Sampling used a random method three times. Observation of morphological characters used 90 and nine fishes for molecular characters-12S rRNA genes. The study used a descriptive technique for data analysis. The results showed that the fish is only one species and suspected consists of 3 variants. Three variants of fish have the same 12S rRNA genes with a fragment size of approximately 1000 bp. The morphological classification of the three groups of fish does not indicate the number of species, but no more as genetic variants.